2016
DOI: 10.1007/s12155-016-9767-6
|View full text |Cite
|
Sign up to set email alerts
|

Initial Effects of Fertilization and Canopy Management on Flowering and Seed and Oil Yields of Jatropha curcas L. in Malawi

Abstract: Appropriate canopy management, including planting density and pruning, and application of fertilizer may increase flowering success and seed and oil yields of Jatropha curcas L. Two field experiments were performed from 2009 to 2011 in Balaka, Malawi, to assess the effect of planting density and pruning regime and single fertilizer application (N, P, and K) on male and female flower number and seed and oil yields of J. curcas. Planting density influenced flower sex ratio and female flower number. Branch prunin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Our results evidenced direct benefits of NPK fertilization on jatropha leaf production and expansion, mainly in plants grown with no MDS (Figure 1). Recent studies investigated NPK effects on this species and have also demonstrated effective response of jatropha plants to NPK fertilization (LIMA et al, 2016;NEGUSSIE et al, 2016). In contrast, chlorophyll index in MDS-treated plants slightly varied due to NPK doses, showing high SPAD values even with no incorporation of NPK into the soil ( Figure 1C).…”
Section: Growth Parameters Leaf Chlorophyll Content and Biomass Allomentioning
confidence: 93%
See 2 more Smart Citations
“…Our results evidenced direct benefits of NPK fertilization on jatropha leaf production and expansion, mainly in plants grown with no MDS (Figure 1). Recent studies investigated NPK effects on this species and have also demonstrated effective response of jatropha plants to NPK fertilization (LIMA et al, 2016;NEGUSSIE et al, 2016). In contrast, chlorophyll index in MDS-treated plants slightly varied due to NPK doses, showing high SPAD values even with no incorporation of NPK into the soil ( Figure 1C).…”
Section: Growth Parameters Leaf Chlorophyll Content and Biomass Allomentioning
confidence: 93%
“…Studies with different fertilization strategies have indicated that jatropha requires significant amounts of nutrients to obtain satisfactory yields. Negussie et al (2016) observed significant responses of jatropha to fertilization, especially with nitrogen, resulting in increased yield. In addition, Lima et al (2016) reported that phosphate and organic fertilization together beneficially influenced plant height, number of branches, stem diameter, leaf area, number of seeds per plant, and total mass of jatropha seeds.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The higher LA values observed in response to NPK incorporation evidenced direct benefits on jatropha leaf production and expansion (Figure 2A). Similarly, recent studies in the literature have investigated NPK effects on jatropha, from early development through final yield, which have demonstrated effective response of this species to NPK fertilization (LIMA et al, 2016;NEGUSSIE et al, 2016).…”
Section: Leaf Area Chlorophyll and Source-sink Relationsmentioning
confidence: 99%
“…Jatropha (Jatropha curcas L.) is considered an important tropical biofuel plant. It is claimed that this species can be grown on soils with low nutrient content, but Negussie et al (2016) have revealed in their recent study that yield is significantly low in non-fertilized trees. In contrast, for Lima et al (2016), jatropha is a perennial species that requires expressive amounts of nutrients to produce satisfactorily.…”
Section: Introductionmentioning
confidence: 99%